Ubiquilin 1 interacts with Orai1 to regulate calcium mobilization - Lee, Jeong-Eun; Jeon, In-Sook; Han, Na-Eun; Song, Hye-Jin; Kim, Eung-Gook; Choi, Jae-Woon; Song, Ki-Duk; Lee, Hak-Kyo; Choi, Joong-Kook (Molecules and cells, 2013)
Store-operated calcium entry (SOCE) channels composed of Stim and Orai proteins play a critical role in diverse biological processes. Upon endoplasmic reticulum (ER)-mediated calcium (Ca 2+ ) depletion, Stim proteins oligomerize with Orai to initiate Ca 2+ influx across the plasma membrane. The ubiquitin-like (UBL) and ubiquitin-associated (UBA) domains of ubiquilin 1 are involved in the degradation of presenilin and polyglutamine proteins. Through screening of Orai1 interaction partner(s) that might have an effect on SOCE, ubiquilin 1 was identified as a target of Orai1. However, the UBL and UBA domains of ubiquilin 1 were dispensable for this interaction. Additionally, ubiquilin 1 and Orai1 colocalized in the cytosolic compartment. Ubiquilin 1 increased the ubiquitination of Orai1, resulting in the formation of a high-molecular-weight form. MG132, a proteasome inhibitor, failed to block the degradation of Orai1, whereas bafilomycin A, a lysosome inhibitor, prevented Orai1 degradation. Confocal microscopy studies demonstrated that a fraction of Orai1 colocalized with ubiquilin 1 and the autophagosomal marker LC3. Because Orai1 is a constituent of SOCE, we determined the effect of ubiquilin 1 on Orai1-mediated Ca 2+ influx. As we expected, intracellular Ca 2+ mobilization, a process normally potentiated by Orai1, was downregulated by ubiquilin 1. Taken together, these findings suggest that ubiquilin 1 downregulates intracellular Ca 2+ mobilization and its downstream signaling by promoting the ubiquitination and lysosomal degradation of Orai1.